Schools’ Records: A Deficiency Analysis of English Language Exercises in Public Schools - Gladday, Ataisi Emiya (Richtmann Publishing, 2012)
This paper examines students’ records of English language exercises in public schools in Rivers State,Nigeria. Students’ record shows classroom practices or interaction between teachers and students as itrelates to the implementation of the national policy on education. Students and teachers in publicsecondary school constitute the population of this study. Data for the study was got through contentanalysis of 30 English language notes from 30 students in five secondary schools in Rivers State. Structuredinterview was also used to elicit data from 15 English language teachers and 72 students in publicsecondary schools to corroborate the students’ record. Simple frequency and percentage are used for dataanalysis. Based on the findings, the paper reveals amongst others that students’ lacks as a result of thequality of language instruction is majorly responsible for students’ proneness to examination malpracticesand mass failure in English language in NECO and WAEC. The paper recommends the provision of anoptimal learning environment for language learning as well as the use of a good supervisory technique toensure instructional quality in language arts in public schools in Rivers State.